2022
DOI: 10.1155/2022/3336941
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Metabolic Regulation and the Microbiota Composition after Supplementation with Different Fatty Acids in db/db Mice

Abstract: Introduction. The effects of fatty acids on health vary and depend on the type, amount, and route of consumption. EPA and DHA have a defined role in health, unlike coconut oil. Objective. The aim was to investigate the changes in metabolic regulation and the composition of the culture-dependent microbiota after supplementation with different fatty acids in db/db mice. Material and Methods. We were using 32 8-week-old db/db mice, supplemented for eight weeks with EPA/DHA derived from microalgae as well as cocon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…Furthermore, this study focused only on the important thermogenesis marker expression profile in BAT, rather than WAT. More importantly, a growing body of research has shown that diet alters crosstalk between the gut microbiota and host metabolism (47)(48)(49). Therefore, the mechanism of regulating obesity and related syndromes by modifying gut microorganisms with CO is worth further development.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this study focused only on the important thermogenesis marker expression profile in BAT, rather than WAT. More importantly, a growing body of research has shown that diet alters crosstalk between the gut microbiota and host metabolism (47)(48)(49). Therefore, the mechanism of regulating obesity and related syndromes by modifying gut microorganisms with CO is worth further development.…”
Section: Discussionmentioning
confidence: 99%